2006
DOI: 10.1124/jpet.106.112003
|View full text |Cite
|
Sign up to set email alerts
|

Fe(III) Shifts the Mitochondria Permeability Transition-Eliciting Capacity of Mangiferin to Protection of Organelle

Abstract: Mangiferin acts as a strong antioxidant on mitochondria. However, when in the presence of Ca 2ϩ , mangiferin elicits mitochondrial permeability transition (MPT), as evidenced by cyclosporin A-sensitive mitochondrial swelling. We now provide evidence, by means of electrochemical and UV-visible spectroscopical analysis, that Fe(III) coordinates with mangiferin. The resulting mangiferin-Fe(III) complex does not elicit MPT and prevents MPT by scavenging reactive oxygen species. Indeed, the complex protects mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
2
23
0
2
Order By: Relevance
“…Reduced glutathione (GSH) and oxidized glutathione (GSSG) were measured spectrofluorimetrically (350-nm excitation wavelength and 420-nm emission wavelength) in the homogenate using the o-phthalaldehyde (OPT) assay as described previously [28]. GSH levels were estimated by a fluorescence-based assay.…”
Section: Glutathione Assaymentioning
confidence: 99%
“…Reduced glutathione (GSH) and oxidized glutathione (GSSG) were measured spectrofluorimetrically (350-nm excitation wavelength and 420-nm emission wavelength) in the homogenate using the o-phthalaldehyde (OPT) assay as described previously [28]. GSH levels were estimated by a fluorescence-based assay.…”
Section: Glutathione Assaymentioning
confidence: 99%
“…It was been found that Mgf preserves the integrity of mitochondrial membrane by protecting it from lipid peroxidation. [28]. Mgf, by scavenging these reactive species, maintains cellular integrity, thus minimizing the possible damage to erythrocytes [4].…”
Section: Mechanism Of Action: As An Antioxidantmentioning
confidence: 99%
“…They showed the formation of a mangiferin:Fe(III) complex (2:1) with the help of changes in electronic spectra as well as by reduction of the anodic current peak in the voltammogram of the compound. The complex was found to be superior antioxidant than mangiferin alone which reacted rather easily with horseradish peroxidase/H 2 O 2 as compared to mangiferin alone [59]. The above group has suggested the ironcomplexing ability of mangiferin (10 µM) as the principal means of protection of rat liver mitochondria against lipid peroxidation mediated by Fe( 2+ )-citrate (50 µM).…”
Section: Reactions Of Mangiferinmentioning
confidence: 95%
“…It has also been reported to increase the ability of mangiferin to scavenge the 2,2-diphenyl-1-picrylhydrazyl radical markedly and exhibit antioxidant action towards H 2 O 2 production, mediated by antimycin A and mitochondrial membrane lipid peroxidation caused by t-butyl hydroperoxide. These researchers also demonstrated that a mixture of Vimang (Mangifera indica L. extract) and Fe(III) is an effective antioxidant and cytoprotective agent [59]. They showed the formation of a mangiferin:Fe(III) complex (2:1) with the help of changes in electronic spectra as well as by reduction of the anodic current peak in the voltammogram of the compound.…”
Section: Reactions Of Mangiferinmentioning
confidence: 95%